Platelet Indices in Neonates: A Comparative Study of Normal and Low Birth Weight Babies - Duggal, Tegsimran; Maini, Baljeet; Chauhan, Gauri; Gaur, Bablu Kumar; Sharma, Mukti; Bhardwaj, Anand Kumar (Journal of Nepal Paediatric Society, 2019)
Introduction: Birth weight is an important indicator of perinatal and neonatal outcome. Low birth weight (LBW) babies suffer from many problems in neonatal period and have more morbidity and mortality as compared to normal weight babies. Platelets play an important role in neonatal immunity. Platelet indices of LBW babies are not well understood and may have contributed to morbidities in these babies. This study was conducted to study the platelet indices in LBW babies. Methods: All inborn LBW babies born in our centre and fulfilling the inclusion criteria were enrolled in the study. Study period was of one and half years (Oct 2015 – Apr 2017). Cord blood sample (2 ml) was collected and platelet indices namely Platelet Count (PC), Mean Platelet Volume (MPV), Platelet Distribution Width (PDW), were assessed. Blood sample was processed with a hospital laboratory based automated analyser. Neonatal morbidities were recorded. Platelet indices were analysed with respect to low birth weight. Results: The platelet count in LBW babies was lower than the control group. Other indices i.e. PDW and MPV however did not show significant variation between both the groups. Conclusions: LBW babies had lower platelet counts but other platelet indices were not significantly affected. The results need to be substantiated with further larger studies in the future.